(untitled) (Journal of Civil Engineering Researchers, 2025)
One of the ways to dispose of urban waste is to burn it in incinerators. In this research, it was tried to use the ash obtained from the waste incineration plant of Saveh city (Iran) as a substitute for part of the consumed cement in concrete production. To achieve this goal, the effects of waste ash on compressive strength, abrasion resistance, flexural strength, water absorption and unit weight of concrete were investigated using experimental methods. The concrete used was made with a compressive strength of 30 MPa. The results obtained from the laboratory tests showed that the addition of waste ash as a partial substitute of the cement in the amounts of 10, 20, and 30% in the tested concrete samples caused to decrease the compressive strength by 21, 42, and 49%, the flexural strength by 5, 15 and 22%, and the unit weight of concrete by 3, 5 and 7% respectively, and to increase the water absorption by 3, 6 and 12% respectively, compared to the control sample. Also, there is a slight decrease in the abrasion resistance of concrete including waste ash. However, the obtained strengths were still acceptable for the construction of concretes that require less strength. On the other hand, the use of this ash as a part of the cement used in concrete not only removes the concern of waste incineration plants to dispose of this pollution, but also reduces the consumption of cement and consequently reduces greenhouse gases caused by cement production.